Differential Adaptation Strategies to Climate Change in African Cropland by Agro-Ecological Zones - Seo, Niggol (World Bank, Washington, DC, 2012)
This paper quantifies how African farmers have adapted their crop and irrigation decisions to their farm's current agro-ecological zone. The results indicate that farmers carefully consider the climate and other conditions of their farm when making these choices. These results are then used to forecast how farmers might change their irrigation and crop choice decisions if climate changes. The model predicts African farmers would adopt irrigation more often under a very hot and dry climate scenario but less often with a mild and wet scenario. However, farms in the deserts, lowland humid forest, or mid elevation humid forest would reduce irrigation even in the very hot and dry climate scenario. Area under fruits and vegetables would increase Africa-wide with the very hot and dry climate scenario, except in the lowland semi-arid agro-ecological zone. Millet would increase overall under the mild and wet scenario, but decline substantially in the lowland dry savannah and lowland semi-arid agro-ecological zones. Maize would be chosen less often across all the agro-ecological zones under both climate scenarios. Wheat would decrease across Africa. The authors recommend that care must be taken to match adaptations to local conditions because the optimal adaptation would depend on the agro-ecological zone and the climate scenario.